Distributional chaos for continuous mappings of the circle - Málek, Michal (Annales Mathematicae Silesianae, 1999)
We show that theory of distributional chaos for continuous functions on the unit interval as developed recently by Schweizer and Smítal remains essentially true for continuous mappings of the circle, with natural exceptions.